Studi kata Aku Tersenyum Berdasarkan Ayub 29:24-25 dan Implementasinya bagi Pemimpin untuk Menguatkan Hati Umat - Titus Titus (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
The lives of many people are currently haunted by anxiety and fear due to the COVID-19 outbreak that has hit the world since the beginning of 2020 until now. People feel hopeless and powerless to live life. This situation is also experienced by believers in every local church. A restless heart, a fading spirit, requires hope and a new positive aura from a leader. The book of Job 29:24-25 provides a record of the experience of a leader who is able to awaken and strengthen the hearts of his people through a smile so that this text becomes an interesting study to be implemented by Christian leaders today. The research method used is literature study, collecting and researching primary and secondary sources from books related to the topics of this paper. So the results of the study show that the smile and spirit of a leader have a positive effect and can strengthen and develop the spirit of the people they lead.